Educar para cuidar e proteger: uma prática reparadora da dignidade infantil - Quadros, Vanessa Salete Bicigo de (2024)
This dissertation is entitled Guinea-Bissau: an Analysis of the Management System in Public Schools and its scope is to discuss issues linked to the Guinean educational system, in particular, the school management system, and reflect on its past (periods pre-colonial, colonial and post-colonial) to understand the process of creating schools and their management. The Guinean educational system, in particular public schools, has faced many difficulties in terms of functioning over time, with successive strikes, lack of infrastructure to house students, lack of minimum conditions for the proper functioning of classes and better achievement by students, not to mention teachers. The structure and the educational system itself are very centralized. This made adapting to regional characteristics increasingly difficult, limiting community participation and inclusion in the school environment. In addition to these successive challenges, government falls, changes in school management and the non-continuity of previous managers' projects demarcate determining elements of the process. It is believed that a stable and participatory management model can help improve the functioning of the school. With this idea, the following question arises: What management concepts are evident in the guidelines of the Ministry of Education and in the way management is carried out in schools in Guinea-Bissau? What form of management could best contribute to qualifying educational work in schools? What is the role of the Regional Education Office in the management of schools? The dissertation adopted as its general objective to analyze the functioning of public school management in Guinea-Bissau and identify the management concepts that are present in it. In a more targeted way, we aim to: analyze the school management system based on documents from the Ministry of Education; identify the policies implemented by the Ministry of Education regarding school management; understand how the school management system for basic and secondary education (elementary and high school) works in a public school in the city of Bissau; identify the perspectives of school management and implications for its organization; know, through observation at school and analysis of ME documents (Ministry of Education, Regional Education Office and school), the projects aimed at school management and proposals for education; verify the political-administrative and pedagogical organization of the school, as well as the operation of its pedagogical administrative autonomy. To answer the questions raised above, we analyzed the documents that guide the management of Guinean schools (Basic Law of the Educational System and Internal Regulations of the observed school), the composition of the structure of the Ministry of Education, the Regional Education Office and the structure of the school. Regarding the methodological issue, the research contemplates a qualitative approach in the field of educational policy, with a reflective analysis regarding Guinean school management policy, through bibliographical and documentary research and, finally, field research carried out by means of observation at school. In conclusion, it is assumed that the Guinean education system still presents an unconsolidated school model, due to the non-compliance with free unified basic education, inadequate infrastructure for the teaching and learning process of students, the non-consolidation of language of instruction and non-compliance with the academic year calendar. On the other hand, the management of Guinean education needs and must be rethought from the Ministry of Education to reach the schools and their separation from party politics.